Arrival-based equalizer for underwater communication systems - Ijaz, S. (2014)
One of the challenges in the present underwater acoustic communication systems is to combat the underwater channel effects which results in time and frequency spreading of the transmitted signal. The time spreading is caused by the multipath effect while the frequency spreading is due to the time variability of the underwater channel. The passive Time Reversal (pTR) equalizer has been used in underwater communications because of its time focusing property which minimizes the time spreading effect of the underwater channel. In order to compensate for the frequency spreading effect, an improved version of pTR was proposed, called Frequency shift passive time reversal (FSpTR). FSpTR tries to compensate for the frequency spreading by applying a frequency shift in the estimated channel impulse response (IR). In the multipath environment, multiple replicas of the transmitted signal reaches the receiver through different paths where each path is affected differently by environmental variations. In such cases, a single frequency shift fails to compensate for the environmental variations on each path, resulting in degradation in the performance. In this paper, an arrival-based equalizer is proposed to compensate for the environmental variations on each path. The concept of beamforming is integrated with FSpTR equalizer, in this paper, to compensate each arrival separately for the environmental variations. The proposed equalizer is tested with the real data and the results showed that the proposed approach outperforms pTR and FSpTR equalizers and provides a mean MSE gain of 4.9 dB and 4.2 dB respectively.